(untitled) (Journal of the College of Languages (JCL), 2019)
This paper tackles methods of teaching conversation in Russian to students speaking Arabic. It analyses the differences between the two languages, as well as the difficulties and major errors faced by Arabic speakers studying Russian. Particularly, it looks at the difficulty of transforming spoken language. Finally, the paper suggests ways for teaching spoken language and treating the reasons behind making errors. Аннотация Данная статья рассматривает методы преподавания говорения на русском языке для носителей арабского языка. В статье анализируются различия двух языков, а также основные проблемы и ошибки, с которыми сталкиваются носители арабского языка при изучении русского, в частности воспроизведения устной речи. Наконец, статья предлагает методы, направленные на обучение устной речи и устранению причин, по которым совершаются ошибки.